Production, characteristics, and applications of microbial-derived fats: halal issues - Mohamed Salih, Noura Karamalla; Mirghani, Mohamed Elwathig Saeed; Daoud, Jamal I. (AIJR, 2025)
This chapter "Microbial Fats" explores the rapid advancement of biotechnology and its application in producing fats and oils via microbial processes. This approach leverages fermentation and bioengineering techniques using diverse microorganisms, including algae, bacteria, yeast, and fungi, to accumulate oils, fatty acids, and triglycerides under specific cultivation conditions. Known as single-cell oils (SCOs), these microbial fats mirror plant oils in structure and can be tailored by adjusting growth conditions, offering promising alternatives for various industries such as food, cosmetics, pharmaceuticals, biofuel, and chemicals. The microbial production of oils has historical roots dating back to the 19th century, with renewed interest in their commercial potential due to their cost-effectiveness, reliance on non-arable feedstocks, and alignment with sustainable practices. Additionally, microbial fats, particularly Omega-3 fatty acids, are recognized for their nutritional benefits and increasing consumer demand as vegan sources of essential fatty acids. This chapter highlights the economic and environmental advantages of microbial fats, such as reduced land use and waste management synergy, while discussing the impact of microbial lipids on sustainable biofuel production, environmental conservation, and the circular economy. The chapter also addresses the importance of ensuring microbial fats’ halal certification to meet global Muslim consumer demand. Ultimately, microbial fats represent a renewable, environmentally friendly alternative to conventional fats, though challenges remain in optimizing production, scalability, and cost-effectiveness.